Amateur filmmaking : the home movie, the archive, the web - Rascaroli, Laura; Young, Gwenda; Monahan, Barry (New York : Bloomsbury, 2014)
With the advent of digital filmmaking and critical recognition of the relevance of self expression, first-person narratives, and personal practices of memorialization, interest in the amateur moving image has never been stronger. Bringing together key scholars in the field, and revealing the rich variety of amateur filmmaking, from home movies of Imperial India and film diaries of life in contemporary China, to the work of leading auteurs such as Joseph Morder and Peter Forgacs, Amateur Filmmaking highlights the importance of amateur cinema as a core object of critical interest across an array of disciplines. With contributions on the role of the archive, on YouTube, and on the impact of new technologies on amateur filmmaking, these essays offer the first comprehensive examination of this growing field.
Introduction. Amateur filmmaking: New developments and Directions -- Section One: Reframing the home movie -- The home movie and space of communication / Roger Odin -- Home movies and amateur film as national cinema / Liz Czach -- The Photographic hangover: reconsidering the aesthetics of the postwar 8mm home movie / Maija Howe -- Amateur film, automobility and the cinematic aesthetics of leisure / Mark Neumann. Section Two: Private reels, historiographical concerns -- Cinemas of catastrophe and continuity: Mapping out Twentieth-century amateur practices of intentional history-making in northern England / Heather Norris Nicholson -- Glimpses of a hidden history: Exploring Irish amateur collections, 1930-1970 / Gwenda Young -- Uncensored British imperial politics in late colonial home movies: Memsahibs, Indian bearers and Chinese communist insurgents / Annamaria Motrescu-Mayes -- The amateur film: From artifact to anecdote / Karen Lury -- Starring Sally Peshlakai: Rewriting the script for Tad Nichols's 1939 Navajo Rug Weaving / Janna Jones. Section Three: Nonfictional Recontextualisations -- Change of scale: Home movies as microhistory in documentary films / Efren Cuevas -- Creating historiography: Alan Gilsenan's formal reframing of amateur archival footage in Home Movie Nights / Barry Monahan -- "That Would Be Wrong": Errol Morris and his use of home movies (as metalanguages) in feature documentaries / Stefano Odorico. Section Four: Amateur Auteur --: "I am a Time Archaeologist": Some reflections on the filmmaking practice of Péter Forgács / Richard Kilborn -- Representing the past and the meaning of home in Péter Forgács's Private Hungary / Ruth Balint -- Necessity is the mother of invention, or Morder's amateur toolkit / Dominique Bluher --: Joseph Morder, the "Filmateur": An interview with Joseph Morder / Dominique Bluher --: Working at home: Tarnation, amateur authorship, and self-inscription in the digital age / Laura Rascaroli. Section Five: New Directions: The Digital Age -- Saving private reels: Archival practices and digital memories (formerly known as home movies) in the digital age / Susan Aasman -- The Home Movie Archive Live / Patricia R. Zimmerman -- An inward gaze at home: Amateur first person DV Documentary filmmaking in Twenty-First century China / Tianqi Yu -- Shooting for profit: The monetary logic of the YouTube home movie / Lauren S. Berliner -- Home movies in the age of Web 2.0: The case of "Star Wars Kid" / Abigail Keating -- Towards mobile filmmaking 2.0: Amateur filmmaking as an alternative cultural practice / Max Schleser.
Bibliografija.
Kazalo.
Keywords: Amaterski film; Dokumentarni film; Digitalna kinematografija; Nove filmske tehnologije